2021
DOI: 10.25035/pad.2021.01.009
|View full text |Cite
|
Sign up to set email alerts
|

“If Others Are Honest, I Will Be Too”: Effects of Social Norms on Willingness to Fake During Employment Interviews

Abstract: Applicant faking in employment interviews is a pressing concern for organizations. It has previously been suggested that subjective norms may be an important antecedent of faking, but experimental studies are lacking. We report a preregistered experiment (N = 307) where effects of conveying descriptive social norms (information about what most applicants do) on self-reported willingness to fake were examined. Although we observed no difference between the faking norm condition and the control condition, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…This experimental manipulation closely resembles those used in several previous norm experiments (e.g., Agerström et al, 2016;Goldstein et al, 2008;Sinclair & Agerström, 2021). In order to encourage participants to pay attention to the manipulation, they had to wait 10 seconds before they could proceed to the next page, and they were also exposed to a reminder of the importance of reading the text thoroughly.…”
Section: Participants Design and Proceduresmentioning
confidence: 99%
“…This experimental manipulation closely resembles those used in several previous norm experiments (e.g., Agerström et al, 2016;Goldstein et al, 2008;Sinclair & Agerström, 2021). In order to encourage participants to pay attention to the manipulation, they had to wait 10 seconds before they could proceed to the next page, and they were also exposed to a reminder of the importance of reading the text thoroughly.…”
Section: Participants Design and Proceduresmentioning
confidence: 99%
“…In general, people thus tend to care about the social norms that surround them—what other people do or think. Indeed, research attests that the activation of social norms can encourage a wide range of either positive or negative behaviors, depending on whether the norm describes an ethical or unethical behavior (e.g., Goldstein et al, 2008; Reid et al, 2010; Sinclair & Agerström, 2023; 2021; Walters & Neighbors, 2005). Throughout the lifespan, people are constantly surrounded by rules, standards, and expectations that direct all aspects of social behavior (Anderson & Dunning, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have more directly examined norms and their findings suggest that norms can indeed be an important antecedent to harmful work behaviors. A recent experimental study found that intentions to fake employment interviews were directly influenced by descriptive norms about whether most people use faking tactics or are honest (Sinclair & Agerström, 2021). Further, several non‐experimental studies have examined the relationship between self‐reported perceived social norms and counterproductive work behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Since faking behaviors can be present before the interview stage and honest candidates usually adopt fewer faking behaviors on their social media (Myers et al, 2021), they might receive fewer interview invitations from the recruiters and sourcers compared to less honest candidates. Some situational factors can also have an effect, such as social norms (knowing about what most applicants do, Sinclair & Agerstrom, 2021) and organizational cultures (such as the competitive culture, Canagasuriam & Roulin, 2021). In one study, when participants were convinced that other participants were honest during the interview, they were less willing to fake even when faking can grant them advantages in interview ratings (Sinclair & Agerstrom, 2021).…”
Section: Understanding How Faking Is Harmfulmentioning
confidence: 99%
“…Some situational factors can also have an effect, such as social norms (knowing about what most applicants do, Sinclair & Agerstrom, 2021) and organizational cultures (such as the competitive culture, Canagasuriam & Roulin, 2021). In one study, when participants were convinced that other participants were honest during the interview, they were less willing to fake even when faking can grant them advantages in interview ratings (Sinclair & Agerstrom, 2021). In addition, the faking-is-good perspective is psychometrically flawed (Burns & Christiansen, 2011;Robie & Christiansen, 2021) especially when the faking is severe (Choi, et al, 2011), and can be harmful to person-environment fit relevant assessments 1 (Charbonneau et al, 2021) where the intention is to find the best-fitting employees, not the brightest employees (Tett & Simonet, 2021).…”
Section: Understanding How Faking Is Harmfulmentioning
confidence: 99%